Effects of ibuprofen on molecular markers of cartilage and synovium turnover in patients with knee osteoarthritis. Issue 7 (11th June 2004) - Gineyts, E; Mo, J A; Ko, A; Henriksen, D B; Curtis, S P; Gertz, B J; Garnero, P; Delmas, P D
Abstract : Objective: The aim of this study was to evaluate the effect of ibuprofen on the urinary excretion of C-terminal crosslinking telopeptide of type II collagen (CTX-II) and urinary glucosyl galactosyl pyridinoline (Glc-Gal-PYD), two new molecular markers of cartilage and synovial tissue metabolism, respectively, in patients with knee osteoarthritis (OA). Methods: We studied 201 patients with knee pain and radiographic evidence of knee OA who were on treatment with non-steroidal anti-inflammatory drugs (NSAIDs) prior to study initiation. After an initial screening visit, patients were withdrawn from their pre-study NSAID and, following a flare of their OA symptoms, were randomised to ibuprofen (2400 mg/day) or placebo. Urinary CTX-II and Glc-Gal-PYD levels were measured at time of randomisation (baseline) and after 4–6 weeks of treatment. Results: After 4 to 6 weeks, urinary CTX-II (+17%, p = 0.023) and Glc-Gal-PYD (+10%, p = 0.020) increased significantly from baseline in the placebo group whereas marginal or no increase was observed in the ibuprofen group (CTX-II +2%, NS and Glc-Gal-PYD +4%, p = 0.045). For urinary CTX-II, the difference in the change from baseline between placebo and ibuprofen treated groups was significant (13%, p = 0.017). At baseline, urinary levels of CTX-II and Glc-Gal-PYD were higher in patients with knee swelling (n = 127) than in those without (n = 74) (p<0.02 for both markers). When patients were stratified according to presence or absence of knee swelling at baseline, the increases over 4–6 weeks of urinary CTX-II and Glc-Gal-PYD in the placebo group were restricted to patients with knee swelling (+22% from baseline, p = 0.001 and +12%, p = 0.011, for urinary CTX-II and Glc-Gal-PYD respectively). In patients with knee swelling who were treated with ibuprofen this increase was not observed and the difference from placebo was significant for urinary CTX-II (p = 0.014). Conclusion: In patients with a flare of knee OA, specifically in patients with evidence of joint inflammation documented by knee swelling, there was a significant increase in markers reflecting cartilage and synovium metabolism that could partly be prevented by high doses of ibuprofen. These data suggest that patients with a flare of knee OA are characterised by increased cartilage and synovial tissue degradation, which may be partly prevented by high doses of NSAIDs.